2001
DOI: 10.1080/713932752
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Control of Appetitive Conditioning: Influence of a Contextual Stimulus Generated by a Partial Reinforcement Procedure

Abstract: Three experiments with rat subjects examined the effects of a context switch after conditioning treatments in which the conditioned stimulus (CS) was either paired with food on every presentation (continuous reinforcement) or on some of its presentations (partial reinforcement). In each experiment, a target CS was given one of these treatments in Context A, and another CS was given a treatment during sessions that were intermixed in Context B. Final tests of the target CS in Context A and Context B often revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 27 publications
4
40
1
3
Order By: Relevance
“…A number of recent experiments have demonstrated that the operant response is reliably weakened when it is tested in a new context (e.g., Bouton et al, 2011; Bouton, Todd, & Léon, 2014; Todd, 2013). Control of operant responding by the acquisition context contrasts with many failures in our hands to observe effects of changing the context after appetitive and aversive Pavlovian learning (e.g., Bouton, Frohardt, Sunsay, Waddell, & Morris, 2008; Bouton & King, 1983; Bouton & Peck, 1989; Bouton & Sunsay, 2001; Bouton & Swartzentruber, 1986; Brooks & Bouton, 1993; Swartzentruber & Bouton, 1986). The relative lack of a context switch effect on Pavlovian acquisition learning appears general across laboratories (Bevins & Ayres, 1992; Grahame, Hallam, Geier, & Miller, 1990; Harris, Jones, Bailey, & Westbrook, 2000; Kaye & Mackintosh, 1990; Leaton, 1974; Lovibond, Preston, & Mackintosh, 1984; Neumann, 2006; Thomas, et al, 2003).…”
Section: Contextual Control Of the Nonextinguished Operant Responsementioning
confidence: 63%
“…A number of recent experiments have demonstrated that the operant response is reliably weakened when it is tested in a new context (e.g., Bouton et al, 2011; Bouton, Todd, & Léon, 2014; Todd, 2013). Control of operant responding by the acquisition context contrasts with many failures in our hands to observe effects of changing the context after appetitive and aversive Pavlovian learning (e.g., Bouton, Frohardt, Sunsay, Waddell, & Morris, 2008; Bouton & King, 1983; Bouton & Peck, 1989; Bouton & Sunsay, 2001; Bouton & Swartzentruber, 1986; Brooks & Bouton, 1993; Swartzentruber & Bouton, 1986). The relative lack of a context switch effect on Pavlovian acquisition learning appears general across laboratories (Bevins & Ayres, 1992; Grahame, Hallam, Geier, & Miller, 1990; Harris, Jones, Bailey, & Westbrook, 2000; Kaye & Mackintosh, 1990; Leaton, 1974; Lovibond, Preston, & Mackintosh, 1984; Neumann, 2006; Thomas, et al, 2003).…”
Section: Contextual Control Of the Nonextinguished Operant Responsementioning
confidence: 63%
“…Once the animals reached a criterion performance of >80% for an odor pair for which long-term memory needs to be checked, we performed resistance to memory extinction. This was done to stabilize the memory of an odor pair and is based on the 'Partial reinforcement theory' (Bouton and Sunsay, 2001). The task comprised of 100 trials with 50 trials for S+ and S-each.…”
Section: Resistance To Memory Extinction Taskmentioning
confidence: 99%
“…Abad, Ramos-Álvarez y Rosas (2009) en una tarea de aprendizaje predictivo humano utilizaron un procedimiento de reforzamiento parcial en el que una clave fue seguida de la consecuencia en la mitad de las ocasiones en las que se presentó. Este tipo de entrenamiento podría generar en los participantes un estado interno "N" relacionado con la frustración (Amsel, 1992) o con la huella en la memoria de los ensayos que no van seguidos de la consecuencia (Bouton y Sunsay, 2001;Capaldi, 1967;Pearce, Redhead y Aydin, 1997), que se sumaría al contexto en el que aparece haciéndolo más saliente. En esta línea argumental, Abad et al (2009) encontraron un efecto de cambio de contexto sobre una clave entrenada de manera consistente (X) cuando otra clave (P) recibió entrenamiento parcial en el mismo contexto.…”
Section: 2-efectos De Cambio De Contextounclassified